Polyphenylene sulfide resin composition for automobile cooling parts and automobile cooling parts
Patent Information
- Application Number
- JP2020566302
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-19
- Filing Date
- 2020-11-18
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2040-11-18
AI Technical Summary
【0018】 本発明は、PPS樹脂、ガラス繊維および特定の官能基を有するシラン化合物とを配合し、PPS樹脂の数平均分子量が7,000~14,000であって、前記(A)ポリフェニレンスルフィド樹脂の250℃で5分間、20倍重量の1-クロロナフタレンに溶解してポアサイズ1μmのPTFEメンブランフィルターで熱時加圧濾過した際の残さ量が2.0~5.0重量%であるポリフェニレンスルフィド樹脂組成物が、高い機械的強度と耐不凍液性とを有し、かつ、モールドデポジットの発生も抑制しているという未知なる特性を見いだしたものである。本発明のPPS樹脂組成物は、自動車冷却部品に有用であり、特に、複数の部品を組み合わせた小型·複雑形状を有する自動車冷却部品の用途に有用である。
Smart Images

Figure 0007635552000005 
Figure 0007635552000006 
Figure 0007635552000007
Abstract
Description
[Technical field]
[0001] The present invention provides a PPS resin composition for automobile cooling parts that has extremely excellent antifreeze resistance while maintaining high mechanical strength and that suppresses the occurrence of mold deposits (deposits that adhere to the surface of a mold), and an injection-molded automobile cooling part. [Background technology]
[0002] Polyphenylene sulfide resin (hereinafter referred to as PPS resin) has a good balance of rigidity, heat resistance, hot water resistance, chemical resistance and moldability, and is therefore widely used in electrical and electronic components, water-related parts and automotive parts.
[0003] These applications require mechanical strength, and so far, proposals have been made to reinforce PPS resin with glass fibers and to formulate PPS resin compositions containing a silane compound having a functional group such as an epoxy group.
[0004] In recent years, the number of parts installed in automobiles has increased, and there is a strong need to save space in the engine compartment. As a result, each part is being made smaller, and development is shifting to modules that combine multiple parts rather than a single part and integrate multiple functions. As a result, parts are becoming thinner and have more complex shapes, so high mechanical strength is required.
[0005] Furthermore, PPS resin compositions with excellent antifreeze resistance are used in automotive cooling parts because liquids such as antifreeze flow along the inner walls of the parts. However, as products become more sophisticated, they are exposed to harsher environments, meaning that they require even stronger antifreeze resistance than ever before.
[0006] On the other hand, while PPS resin has a high melting point and excellent heat resistance, the high processing temperature during injection molding causes mold deposits due to the PPS resin and additives, which can lead to poor appearance and reduced dimensional accuracy in molded products, as well as reduced productivity due to the need to disassemble and clean the mold.
[0007] In particular, automotive cooling parts are now being installed in many automobiles in order to improve engine fuel efficiency and optimize battery performance, and improving yield rates and productivity has become a major challenge.
[0008] Therefore, there is a demand for a PPS resin composition for automobile cooling parts which has not only mechanical strength but also hot water resistance and antifreeze resistance and which suppresses the generation of mold deposits. [Prior art documents] [Patent documents]
[0009] For example, Patent Documents 1 and 2 disclose PPS resin compositions in which linear PPS resin is reinforced with glass fibers and a silane compound is blended. Patent Document 3 discloses a PPS resin composition in which glass fibers and a silane compound are blended with a PPS resin obtained by contacting a low-hydration alkali metal sulfide that has been subjected to a specific treatment with a dihalogenated aromatic compound in an organic polar solvent and polymerizing the PPS resin. Patent Document 4 discloses a PPS resin composition in which glass fibers and a silane compound are blended with a PPS resin that is a mixture of a high molecular weight PPS resin having a crosslinked structure and a low molecular weight PPS resin not having a crosslinked structure. [Patent Document 1] JP 2011-153242 A [Patent Document 2] JP 2010-195874 A [Patent Document 3] JP 2006-219666 A [Patent Document 4] Japanese Patent Application Publication No. 6-41425 Summary of the Invention [Problem to be solved by the invention]
[0010] However, although Patent Documents 1 and 2 describe mechanical strength, no specific study was conducted on antifreeze resistance, and the effects of suppressing mold deposit formation were not satisfactory. Patent Document 3 describes mechanical strength, but no specific study was conducted on antifreeze resistance, and the effects of suppressing mold deposit formation were not satisfactory. Furthermore, Patent Document 4 describes mechanical strength, but no specific study was conducted on antifreeze resistance, and the effects of both antifreeze resistance and suppressing mold deposit formation were not satisfactory.
[0011] The present invention provides a PPS resin composition for automobile cooling parts that has extremely excellent antifreeze resistance and suppresses the formation of mold deposits while maintaining high mechanical strength, and also provides an injection-molded automobile cooling part. [Means for solving the problem]
[0012] The polyphenylene sulfide resin composition for automotive cooling parts of the present invention has the following constitution in order to solve the above problems. (A) 100 parts by weight of polyphenylene sulfide resin, (B) 30 to 110 parts by weight of glass fiber, and (C) Isocyanate functional group and 0.1 to 3 parts by weight of a silane compound having the formula: wherein the polyphenylene sulfide resin (A) has a number average molecular weight of 7,000 to 14,000, and the polyphenylene sulfide resin composition for automobile cooling parts has a residue amount of 2.0 to 5.0% by weight when the polyphenylene sulfide resin (A) is dissolved in 1-chloronaphthalene in an amount 20 times by weight at 250°C for 5 minutes and pressure filtered under hot conditions through a PTFE membrane filter having a pore size of 1 µm.
[0013] The automotive cooling component of the present invention has the following configuration. and an automobile cooling part made of the polyphenylene sulfide resin composition.
[0014] The polyphenylene sulfide resin composition for automobile cooling parts of the present invention preferably has a melt crystallization peak temperature of 230° C. or higher.
[0015] The polyphenylene sulfide resin composition for automobile cooling parts of the present invention preferably satisfies both of the following conditions (i) and (ii). (i) Using a type A1 test piece (hereinafter referred to as ISO test piece) specified in ISO 20753 obtained by injection molding a polyphenylene sulfide resin composition, the tensile strength measured in accordance with ISO 527-1 and -2 methods under conditions of a tensile speed of 5 mm / min and an ambient temperature of 23°C is 190 MPa or more. (ii) The ISO test piece is immersed in an antifreeze solution at 150°C for 500 hours, and then the retention of tensile strength measured in accordance with ISO 527-1 and -2 at a tension speed of 5 mm / min and an ambient temperature of 23°C is 80% or more.
[0016] The automobile cooling part of the present invention preferably comprises a housing formed by injection molding the above polyphenylene sulfide resin composition, and at least two pipes.
[0017] The automobile cooling part of the present invention preferably comprises a housing formed by injection molding the above-mentioned polyphenylene sulfide resin composition, a valve, and at least three pipes in combination. Effect of the Invention
[0018] The present invention has discovered an unknown characteristic that a polyphenylene sulfide resin composition, which is a mixture of PPS resin, glass fiber, and a silane compound having a specific functional group, has a number average molecular weight of 7,000 to 14,000, and has a residue amount of 2.0 to 5.0% by weight when dissolved in 1-chloronaphthalene of 20 times the weight of the polyphenylene sulfide resin (A) at 250°C for 5 minutes and pressure filtered through a PTFE membrane filter having a pore size of 1 μm, has high mechanical strength and antifreeze resistance, and also suppresses the occurrence of mold deposits. The PPS resin composition of the present invention is useful for automobile cooling parts, and is particularly useful for automobile cooling parts having small and complex shapes formed by combining multiple parts. [Brief description of the drawings]
[0019] [Figure 1] 1 is a schematic diagram of an automobile cooling component that is composed of a housing and at least two pipes, (a) is a top view, and (b) is a side view. [Diagram 2] 1 is a schematic diagram of an automobile cooling component that combines a housing, a valve, and at least three pipes. [Diagram 3] Schematic diagrams of a molded product for evaluating mold fouling properties: (a) is a top view, and (b) is a side view. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Hereinafter, an embodiment of the present invention will be described. In the present invention, "weight" means "mass".
[0021] The resin composition of the present invention is a composition containing a polyphenylene sulfide resin (hereinafter referred to as PPS resin) since heat resistance is required.
[0022] The PPS resin (A) used in the present invention is a polymer having a repeating unit represented by the following structural formula:
[0023] [ka]
[0024] From the viewpoint of heat resistance, a polymer containing 70 mol % or more, and more preferably 90 mol % or more, of a polymer containing a repeating unit represented by the above structural formula is preferable. In addition, about 30 mol % or less of the repeating units of the PPS resin may be composed of a repeating unit having the following structure.
[0025] [ka]
[0026] The polyhalogenated aromatic compound, sulfidizing agent, polymerization solvent, molecular weight regulator, polymerization aid and polymerization stabilizer used in the production method of the present invention will be described below.
[0027] [Polyhalogenated aromatic compounds] Polyhalogenated aromatic compounds refer to compounds having two or more halogen atoms in one molecule. Specific examples include polyhalogenated aromatic compounds such as p-dichlorobenzene, m-dichlorobenzene, o-dichlorobenzene, 1,3,5-trichlorobenzene, 1,2,4-trichlorobenzene, 1,2,4,5-tetrachlorobenzene, hexachlorobenzene, 2,5-dichlorotoluene, 2,5-dichloro-p-xylene, 1,4-dibromobenzene, 1,4-diiodobenzene, and 1-methoxy-2,5-dichlorobenzene, and p-dichlorobenzene is preferred. In addition, it is possible to combine two or more different polyhalogenated aromatic compounds to form a copolymer, but it is preferred to use p-dihalogenated aromatic compounds as the main component.
[0028] The amount of the polyhalogenated aromatic compound used is, for example, in the range of 0.9 to 2.0 moles, preferably 0.95 to 1.5 moles, and more preferably 1.005 to 1.2 moles per mole of the sulfidizing agent in order to obtain a PPS resin with a viscosity suitable for processing.
[0029] [Sulfidizing agent] The sulfidizing agent includes alkali metal sulfides, alkali metal hydrosulfides, and hydrogen sulfide.
[0030] Specific examples of alkali metal sulfides include lithium sulfide, sodium sulfide, potassium sulfide, rubidium sulfide, cesium sulfide, and mixtures of two or more of these, with sodium sulfide being preferred. These alkali metal sulfides can be used as hydrates or aqueous mixtures, or in the anhydrous form.
[0031] Specific examples of the alkali metal hydrosulfide include sodium hydrosulfide, potassium hydrosulfide, lithium hydrosulfide, rubidium hydrosulfide, cesium hydrosulfide, and mixtures of two or more of these, with sodium hydrosulfide being preferred. These alkali metal hydrosulfides can be used as hydrates or aqueous mixtures, or in the anhydrous form.
[0032] In addition, a sulfidizing agent prepared in situ in the reaction system from an alkali metal hydrosulfide and an alkali metal hydroxide can also be used. Also, a sulfidizing agent can be prepared from an alkali metal hydrosulfide and an alkali metal hydroxide, and then transferred to a polymerization tank for use.
[0033] Alternatively, a sulfidizing agent prepared in situ in the reaction system from an alkali metal hydroxide such as lithium hydroxide or sodium hydroxide and hydrogen sulfide can be used. Also, a sulfidizing agent can be prepared from an alkali metal hydroxide such as lithium hydroxide or sodium hydroxide and hydrogen sulfide, and then transferred to a polymerization tank for use.
[0034] When a part of the sulfidizing agent is lost before the start of the polymerization reaction due to a dehydration operation or the like, the amount of the charged sulfidizing agent means the remaining amount obtained by subtracting the lost amount from the actual charged amount.
[0035] In addition, it is possible to use an alkali metal hydroxide and / or an alkaline earth metal hydroxide together with the sulfidizing agent.Specific examples of the alkali metal hydroxide include, for example, sodium hydroxide, potassium hydroxide, lithium hydroxide, rubidium hydroxide, cesium hydroxide, and mixtures of two or more of these, and specific examples of the alkaline earth metal hydroxide include, for example, calcium hydroxide, magnesium hydroxide, strontium hydroxide, barium hydroxide, etc., and among these, sodium hydroxide is preferably used.
[0036] When an alkali metal hydrosulfide is used as the sulfidizing agent, it is particularly preferable to use an alkali metal hydroxide simultaneously. The amount of the alkali metal hydroxide used is, for example, in the range of 0.95 to 1.20 mol, preferably 1.00 to 1.15 mol, and more preferably 1.005 to 1.100 mol per mol of the alkali metal hydrosulfide.
[0037] [Polymerization solvent] As the polymerization solvent, it is preferable to use an organic polar solvent. Specific examples include N-alkylpyrrolidones such as N-methyl-2-pyrrolidone and N-ethyl-2-pyrrolidone, caprolactams such as N-methyl-ε-caprolactam, aprotic organic solvents such as 1,3-dimethyl-2-imidazolidinone, N,N-dimethylacetamide, N,N-dimethylformamide, hexamethylphosphoric triamide, dimethylsulfone, and tetramethylene sulfoxide, and mixtures thereof, all of which are preferably used because of their high reaction stability. Among these, N-methyl-2-pyrrolidone (hereinafter sometimes abbreviated as NMP) is particularly preferably used.
[0038] The amount of the organic polar solvent used is usually selected from the range of preferably 2.0 to 10 mol, more preferably 2.25 to 6.0 mol, and further preferably 2.5 to 5.5 mol, per mol of the sulfidizing agent.
[0039] [Molecular weight regulator] A monohalogenated compound (not necessarily an aromatic compound) can be used in combination with the polyhalogenated aromatic compound to form terminals in the resulting PPS resin or to control the polymerization reaction or molecular weight.
[0040] [Polymerization aid] In order to obtain a PPS resin with a relatively high degree of polymerization in a short time, it is also a preferred embodiment to use a polymerization aid. Here, the polymerization aid means a substance that has the effect of increasing the viscosity of the resulting PPS resin. Specific examples of such polymerization aids include organic carboxylate metal salts, water, alkali metal chlorides, organic sulfonates, alkali metal sulfates, alkaline earth metal oxides, alkali metal phosphates, and alkaline earth metal phosphates. These can be used alone or in combination of two or more. Among them, organic carboxylate metal salts and / or water are preferably used.
[0041] The organic carboxylate metal salt is represented by the general formula R(COOM) n (wherein R is an alkyl group, a cycloalkyl group, an aryl group, an alkylaryl group, or an arylalkyl group having 1 to 20 carbon atoms; M is an alkali metal selected from lithium, sodium, potassium, rubidium, and cesium; and n is an integer of 1 to 3). The organic carboxylate metal salt can also be used as a hydrate, anhydride, or an aqueous solution. Specific examples of the organic carboxylate metal salt include lithium acetate, sodium acetate, potassium acetate, sodium propionate, lithium valerate, sodium benzoate, sodium phenylacetate, potassium p-toluate, and mixtures thereof.
[0042] The organic carboxylate metal salt may be formed by adding and reacting an organic acid with one or more compounds selected from the group consisting of alkali metal hydroxides, alkali metal carbonates, and alkali metal bicarbonates in approximately equal chemical equivalents. Among the above organic carboxylate metal salts, sodium acetate is most preferably used because it is inexpensive and has a suitable solubility in the polymerization system.
[0043] When these polymerization aids are used, the amount used is usually in the range of 0.01 mol to 0.7 mol per mol of the charged alkali metal sulfide, and in terms of obtaining a higher degree of polymerization, the range of 0.1 to 0.6 mol is preferable, and the range of 0.2 to 0.5 mol is more preferable.
[0044] The use of water as a polymerization aid is one of the effective means for obtaining a resin composition with a high balance between fluidity and high toughness. In this case, the amount of water added is usually in the range of 0.5 mol to 15 mol per mol of the charged alkali metal sulfide, and in terms of obtaining a higher degree of polymerization, the range of 0.6 to 10 mol is preferable, and the range of 1 to 5 mol is more preferable.
[0045] There is no particular designation for the timing of addition of these polymerization aids, and they may be added at any time during the pre-step, at the start of polymerization, or during the polymerization, as described below, or may be added in several portions, but when an organic carboxylate metal salt is used as the polymerization aid, it is more preferable to add it at the start of the pre-step or at the start of polymerization, because it is easy to add it. When water is used as the polymerization aid, it is effective to add it during the polymerization reaction after the polyhalogenated aromatic compound is charged.
[0046] [Polymerization stabilizer] A polymerization stabilizer can be used to stabilize the polymerization reaction system and prevent side reactions. The polymerization stabilizer contributes to the stabilization of the polymerization reaction system and suppresses undesirable side reactions. One indicator of side reactions is the generation of thiophenol, and the addition of a polymerization stabilizer can suppress the generation of thiophenol. Specific examples of polymerization stabilizers include compounds such as alkali metal hydroxides, alkali metal carbonates, alkaline earth metal hydroxides, and alkaline earth metal carbonates. Among these, alkali metal hydroxides such as sodium hydroxide, potassium hydroxide, and lithium hydroxide are preferred. The above-mentioned organic carboxylate metal salts also act as polymerization stabilizers, and are therefore included in the polymerization stabilizers used in the present invention. In addition, when an alkali metal hydrosulfide is used as a sulfidizing agent, it is particularly preferable to use an alkali metal hydroxide at the same time, as described above. Here, an excess of an alkali metal hydroxide relative to the sulfidizing agent can also serve as a polymerization stabilizer.
[0047] These polymerization stabilizers can be used alone or in combination of two or more. The polymerization stabilizer is preferably used in a ratio of usually 0.02 to 0.2 mol, preferably 0.03 to 0.1 mol, more preferably 0.04 to 0.09 mol, per mol of the charged alkali metal sulfide. Within the above preferred range, the stabilizing effect is sufficient, while being economically advantageous and enabling a high polymer yield.
[0048] The timing of adding the polymerization stabilizer is not particularly specified, and it may be added at any time during the pre-step described below, at the start of polymerization, or during the polymerization, or may be added in several divided portions. However, it is more preferable to add it simultaneously at the start of the pre-step or at the start of polymerization from the viewpoint of ease.
[0049] Next, the pre-process, the polymerization reaction process, and the recovery process will be specifically described in order.
[0050] [Pre-process] The sulfidizing agent is usually used in the form of a hydrate, and it is preferable to heat the mixture containing the organic polar solvent and the sulfidizing agent before adding the polyhalogenated aromatic compound, and remove excess water from the system. If too much water is removed by this operation, it is preferable to add water to make up for the shortage.
[0051] As described above, the sulfidizing agent may be an alkali metal sulfide prepared in situ in the reaction system from an alkali metal hydrosulfide and an alkali metal hydroxide, or in a tank separate from the polymerization tank. There is no particular restriction on this method, but a preferable method is to add an alkali metal hydrosulfide and an alkali metal hydroxide to an organic polar solvent in an inert gas atmosphere at room temperature to 150°C, preferably from room temperature to 100°C, and then heat the mixture to at least 150°C, preferably 180 to 260°C, under normal pressure or reduced pressure, to distill off water. A polymerization aid may be added at this stage. Toluene or the like may be added to promote the distillation of water.
[0052] In the polymerization reaction, the amount of water in the polymerization system is preferably 0.5 to 10.0 mol per 1 mol of the charged sulfidizing agent. Here, the amount of water in the polymerization system is the amount of water charged to the polymerization system minus the amount of water removed from the polymerization system. The charged water may be in any form such as water, an aqueous solution, or water of crystallization.
[0053] [Polymerization reaction process] It is preferable to produce the PPS resin by reacting a sulfidizing agent with a polyhalogenated aromatic compound in an organic polar solvent within a temperature range of 200 to 290°C.
[0054] When starting the polymerization reaction process, the sulfidizing agent and the polyhalogenated aromatic compound are added to the organic polar solvent, desirably in an inert gas atmosphere, at a temperature range of room temperature to 220° C., preferably 100 to 220° C. A polymerization aid may be added at this stage. There is no particular restriction on the order in which these raw materials are charged, and they may be charged simultaneously.
[0055] The mixture is usually heated to a temperature in the range of 200° C. to 290° C. There are no particular limitations on the heating rate, but a rate of 0.01 to 5° C. / min is usually selected, and a range of 0.1 to 3° C. / min is more preferable.
[0056] In general, the temperature is finally raised to 250 to 290° C., and the reaction is carried out at that temperature for usually 0.25 to 50 hours, preferably 0.5 to 20 hours.
[0057] In order to obtain a higher degree of polymerization, it is effective to carry out a reaction at 200° C. to 260° C. for a certain period of time before the final temperature is reached, and then to raise the temperature to 270° C. to 290° C. In this case, the reaction time at 200° C. to 260° C. is usually selected in the range of 0.25 hours to 20 hours, and preferably 0.25 hours to 10 hours.
[0058] In order to obtain a polymer with a higher degree of polymerization, it is effective to carry out the polymerization in multiple stages. When carrying out the polymerization in multiple stages, it is effective to move to the next stage when the conversion rate of the polyhalogenated aromatic compound in the system at 245°C reaches 40 mol% or more, preferably 60 mol%.
[0059] [Recovery process] After the polymerization is completed, solids are recovered from the polymerization reaction mixture containing the polymer, the solvent, and the like.
[0060] A preferred method for recovering PPS resin is to carry out the recovery under rapid cooling conditions, and one preferred recovery method is the flash method. In the flash method, the polymerization reaction product is subjected to high temperature and high pressure (usually 250°C or higher, 8 kg / cm 2 The method is to flash the polymer from the above state into an atmosphere of normal pressure or reduced pressure, recover the solvent, and recover the polymer in powder form at the same time. Flashing here means to eject the polymerization reaction product from a nozzle. Specific examples of the atmosphere for flashing include nitrogen or water vapor at normal pressure, and the temperature is usually selected in the range of 150°C to 250°C.
[0061] The flash method is an economical method because it can recover solids at the same time as the solvent, and the recovery time can be relatively short. In this method, ionic compounds such as Na and organic low-polymerization substances (oligomers) tend to be easily incorporated into the polymer during the solidification process.
[0062] However, the method for recovering the PPS resin used in the production method of the present invention is not limited to the flash method, and a method for recovering a particulate polymer by slow cooling (quench method) may be used as long as the method satisfies the requirements of the present invention. However, from the viewpoint of economy, it is more preferable to use the PPS resin recovered by the flash method.
[0063] [Post-processing process] In the present invention, it is important to subject the PPS resin obtained, for example, through the above-mentioned polymerization reaction step and recovery step to an acid treatment.
[0064] The acid used in the acid treatment in the present invention is not particularly limited as long as it does not have the effect of decomposing the PPS resin, and examples of the acid include acetic acid, hydrochloric acid, sulfuric acid, phosphoric acid, silicic acid, carbonic acid and propylic acid, with acetic acid and hydrochloric acid being more preferably used.
[0065] The water used in preparing the aqueous acid solution is preferably distilled water or deionized water. The aqueous acid solution preferably has a pH of 1 to 7, more preferably a pH of 2 to 4. When the pH is within the above preferred range, an increase in the metal content of the PPS resin can be prevented, while an increase in the volatile components of the PPS resin can be prevented.
[0066] The acid treatment method is preferably to immerse the PPS resin in an acid or an aqueous solution of an acid, and if necessary, stirring and heating can be performed appropriately. The temperature during heating is preferably 80 to 250°C, more preferably 120 to 200°C, and even more preferably 150 to 200°C. When the temperature during heating is within the above-mentioned preferred range, the acid treatment effect is sufficient, and an increase in the metal content is prevented, while the pressure does not become too high, which is preferable from the viewpoint of safety. In addition, the pH of the PPS resin immersed in an aqueous solution of an acid is preferably less than 8 by the acid treatment, and more preferably 2 to 8. When the PPS resin is immersed in an aqueous solution of an acid and treated, the pH is within the above-mentioned preferred range, and an increase in the metal content of the resulting PPS resin can be prevented.
[0067] The acid treatment time is preferably a time sufficient for the reaction between the PPS resin and the acid to reach sufficient equilibrium, and is preferably 2 to 24 hours when treated at 80°C, and preferably 0.01 to 5 hours when treated at 200°C.
[0068] The ratio of the PPS resin to the acid or aqueous acid solution in the acid treatment is preferably such that the PPS resin is sufficiently immersed in the acid or aqueous acid solution, and the amount of the acid or aqueous acid solution per 500 g of PPS resin is preferably 0.5 to 500 L, more preferably 1 to 100 L, and even more preferably 2.5 to 20 L. When the amount of the acid or aqueous acid solution per 500 g of PPS resin is within the above preferred range, the PPS resin is sufficiently immersed in the aqueous solution and can be washed well, preventing an increase in the metal content of the PPS resin, while the amount of solution relative to the PPS resin is appropriate, thereby improving production efficiency.
[0069] These acid treatments are carried out by adding a predetermined amount of PPS resin to a predetermined amount of water and acid, heating and stirring in a pressure vessel, or by continuously performing acid treatment. The method for separating the aqueous solution and the PPS resin from the treatment solution after the acid treatment is simple filtration using a sieve or filter, and examples of such methods include natural filtration, pressure filtration, reduced pressure filtration, and centrifugal filtration. In order to remove the acid and impurities remaining on the surface of the PPS resin separated from the treatment solution, it is preferable to wash the PPS resin several times with water or hot water. Examples of the washing method include a method of filtering the PPS resin on a filter while pouring water on it, or a method of separating the aqueous solution and the PPS resin by adding the separated PPS resin to water prepared in advance and filtering it again. The water used for washing is preferably distilled water or deionized water. It is considered that the structure of the terminals of the PPS resin treated with acid in this way changes, but it is difficult to express the structure of the PPS resin obtained by the acid treatment in a general formula, and it is also difficult to identify it by its characteristics, so it can only be identified by the process (acid treatment) for obtaining the PPS resin.
[0070] In the present invention, it is preferable to carry out hot water treatment before the acid treatment step, and the method thereof is as follows. The water used in the hot water treatment in the present invention is preferably distilled water or deionized water. The hot water treatment temperature is preferably 80 to 250°C, more preferably 120 to 200°C, and even more preferably 150 to 200°C. When the hot water treatment temperature is in the above-mentioned preferable range, the hot water treatment effect is excellent, the amount of volatilized gas generated can be reduced, and on the other hand, the pressure does not become too high, which is preferable from the viewpoint of safety.
[0071] The hot water treatment time is preferably a time that allows sufficient extraction treatment of the PPS resin with hot water, and when treatment is performed at 80°C, it is preferably 2 to 24 hours, and when treatment is performed at 200°C, it is preferably 0.01 to 5 hours.
[0072] The ratio of PPS resin to water in the hot water treatment is preferably such that the PPS resin is sufficiently immersed in water, and is preferably 0.5 to 500 L of water per 500 g of PPS resin, more preferably 1 to 100 L, and even more preferably 2.5 to 20 L. If the amount of water is less than 0.5 L per 500 g of PPS resin, the PPS resin is not sufficiently immersed in water, resulting in poor cleaning and an increased amount of volatilized gas, which is not preferred. If the amount of water is more than 500 L per 500 g of PPS resin, the amount of water is greatly excessive relative to the PPS resin, which is not preferred because it significantly reduces production efficiency.
[0073] There is no particular limit to the operation of these hot water treatments, and the method may be a method of putting a predetermined amount of PPS resin into a predetermined amount of water and heating and stirring in a pressure vessel, or a method of continuously performing hot water treatment. There is no particular limit to the method of separating the aqueous solution and the PPS resin from the treatment solution after the hot water treatment, but filtration using a sieve or filter is convenient, and examples of such methods include natural filtration, pressure filtration, reduced pressure filtration, and centrifugal filtration. In order to remove impurities remaining on the surface of the PPS resin separated from the treatment solution, it is preferable to wash the PPS resin several times with water or hot water. There is no particular limit to the washing method, but examples of such methods include a method of filtering the PPS resin on a filter while pouring water on it, and a method of filtering the PPS resin again after the separated PPS resin is put into water prepared in advance. The water used for washing is preferably distilled water or deionized water.
[0074] In addition, since it is undesirable for the PPS terminal groups to decompose during the acid treatment or hot water treatment, it is desirable to carry out the acid treatment or hot water treatment in an inert atmosphere. Examples of the inert atmosphere include nitrogen, helium, and argon, and from the viewpoint of economy, a nitrogen atmosphere is preferable.
[0075] In the present invention, a step of washing the PPS resin with an organic solvent may be included prior to the step of acid treatment or hot water treatment, and the method is as follows: The organic solvent used in washing the PPS resin in the present invention is not particularly limited as long as it does not have the action of decomposing the PPS resin, and examples of the organic solvent include nitrogen-containing polar solvents such as N-methyl-2-pyrrolidone, dimethylformamide, dimethylacetamide, 1,3-dimethylimidazolidinone, hexamethylphosphoramide, piperazinones, etc.; sulfoxide / sulfone solvents such as dimethyl sulfoxide, dimethyl sulfone, sulfolane, etc.; ketone solvents such as acetone, methyl ethyl ketone, diethyl ketone, acetophenone, etc.; dimethyl ether, dipropyl ether, dioxane, tetrahydrofuran, etc.; Examples of the organic solvent include ether solvents such as fluorofuran, halogen-based solvents such as chloroform, methylene chloride, trichloroethylene, ethylene dichloride, perchloroethylene, monochloroethane, dichloroethane, tetrachloroethane, perchloroethane, and chlorobenzene, alcohol-phenol solvents such as methanol, ethanol, propanol, butanol, pentanol, ethylene glycol, propylene glycol, phenol, cresol, polyethylene glycol, and polypropylene glycol, and aromatic hydrocarbon solvents such as benzene, toluene, and xylene. Among these organic solvents, N-methyl-2-pyrrolidone, acetone, dimethylformamide, and chloroform are particularly preferred. These organic solvents are used alone or in combination of two or more.
[0076] The method of washing with an organic solvent includes immersing the PPS resin in the organic solvent, and stirring or heating can be performed as necessary. There is no particular restriction on the washing temperature when washing the PPS resin with an organic solvent, and any temperature between room temperature and about 300°C can be selected. The higher the washing temperature, the higher the washing efficiency tends to be, but usually a washing temperature between room temperature and 150°C is sufficient. Washing can also be performed under pressure in a pressure vessel at a temperature above the boiling point of the organic solvent. There is also no particular restriction on the washing time. Although it depends on the washing conditions, in the case of batch washing, washing for 5 minutes or more usually produces a sufficient effect. Continuous washing is also possible.
[0077] The acid treatment, hot water treatment and washing with an organic solvent may be carried out in a suitable combination.
[0078] [Heat treatment process] In the present invention, it is preferable to further subject the PPS resin after the above-mentioned post-treatment step to a heat treatment, since this gives a PPS resin having high mechanical strength and excellent antifreeze resistance. The heat treatment step will be specifically described below.
[0079] In the present invention, it is preferable to perform heat treatment in order to obtain a PPS resin having high mechanical strength, but excessive heat treatment is not preferable because it reduces melt fluidity and increases gelled matter in the resin, which can cause underfilling during molding. However, if the heat treatment is too mild, the effect of reducing volatile components is small, the strength of the resin decreases, and the antifreeze resistance also tends to decrease. According to the heat treatment of the present invention, it is possible to obtain a PPS resin with improved mechanical strength while suppressing the generation of gelled matter without impairing melt fluidity.
[0080] The heat treatment may be performed in an atmosphere with a high or low oxygen concentration as long as the heat treatment temperature and time are within specific ranges, but heat treatment in an atmosphere with a low oxygen concentration is preferred.
[0081] The conditions of the high oxygen concentration atmosphere are preferably an oxygen concentration exceeding 2% by volume, and the heat treatment temperature is preferably 160 to 270°C and the heat treatment time is preferably 0.1 to 17 hours. However, under conditions of high oxygen concentration, the reduction rate of volatile components is fast, but at the same time, oxidative crosslinking progresses rapidly, making it easy for gelation to occur. Therefore, it is generally preferable to perform heat treatment at a low temperature for a long time or at a high temperature for a short time. Specific conditions for low-temperature long-term heat treatment are preferably 160°C to 210°C and 1 hour to 17 hours, and more preferably 170°C to 200°C and 1 hour to 10 hours. When the heat treatment temperature during low-temperature long-term heat treatment is in the above-mentioned preferred range, the effect of reducing volatile components is excellent and the effect of improving mechanical strength can be expected, while oxidative crosslinking is unlikely to progress even if the heat treatment time is long under conditions of low temperature and oxygen concentration exceeding 2% by volume, and the generation of gelation can be prevented. Specific conditions for high-temperature, short-time heat treatment are preferably above 210°C and not more than 270°C for 0.1 to less than 1 hour, and more preferably from 220°C to 260°C for 0.2 to 0.8 hours. When the heat treatment temperature during high-temperature, short-time heat treatment is within the above-mentioned preferred range, oxidative crosslinking does not progress rapidly and the generation of gelled matter can be prevented, while even if the heat treatment time is short at a high temperature, the effect of reducing volatile components is sufficient, and an improvement in mechanical strength can be expected.
[0082] The conditions for the low oxygen concentration atmosphere are preferably an oxygen concentration of 2% by volume or less, a heat treatment temperature of 210 to 270°C, and a heat treatment time of 0.2 to 50 hours. Since the effect of reducing volatile components tends to be smaller when the oxygen concentration is low, it is generally preferable to perform the heat treatment at a high temperature for a long time, and more preferably at a heat treatment temperature of 220°C to 260°C for 2 to 20 hours. When the heat treatment time is within the above preferred range, the volatile components are sufficiently reduced, and an effect of improving mechanical strength can be expected, while excellent productivity is achieved.
[0083] The heating device for the heat treatment of the present invention may be a normal hot air dryer, or a heating device with a rotating or stirring blade. However, when the treatment is to be performed efficiently and more uniformly, it is more preferable to use a heating device with a rotating or stirring blade. Examples of such devices include a paddle dryer, a fluidized bed dryer, a KID dryer, a steam tube dryer, an inclined disk dryer, a hopper dryer, and a vertical stirring dryer. Among them, a paddle dryer, a fluidized bed dryer, and a KID dryer are preferable for uniform and efficient heating. In order to adjust the oxygen concentration of the heat treatment, it is no problem to mix a non-oxidizing inert gas such as nitrogen, argon, helium, or water vapor with an oxidizing gas such as oxygen, air, or ozone. As long as the heat treatment can be performed in the heating device, there is no particular restriction on the position from which the oxidizing gas or inert gas is introduced, whether the upper part, lower part, or side part of the heating device. However, a more convenient method is to introduce the gas from the upper part of the heating device. The oxidizing gas and the inert gas may be mixed together before being introduced into the heating device, or the oxidizing gas and the inert gas may be mixed separately from different positions in the heating device.
[0084] It is believed that the structure of the PPS resin changes as a result of the heat treatment process, but the PPS resin obtained through the heat treatment has a complex and diverse structure, and there are circumstances in which it is not practical to specify the structure of the PPS resin. By going through the heat treatment process, it is possible to remove the volatile matter and moisture contained in the PPS resin, and it is possible to obtain a PPS resin that has excellent mechanical strength, weld strength, and antifreeze resistance.
[0085] The melt flow rate (hereinafter sometimes abbreviated as MFR) of the PPS resin obtained through the above polymerization reaction step, recovery step, preferably post-treatment step, and heat treatment step is preferably 1,000 g / 10 min or less, more preferably 700 g / 10 min or less, and even more preferably 500 g / 10 min or less. When the MFR is in the above preferred range, the degree of polymerization is sufficiently high and the mechanical strength is excellent. As for the lower limit, a range exceeding 80 g / 10 min is preferable from the viewpoint of moldability, and 100 g / 10 min or more is preferable. Here, the MFR is a value measured according to ASTM-D1238-70 at a measurement temperature of 315.5° C. and a load of 5,000 g.
[0086] The number average molecular weight of the PPS resin used in the present invention is 7,000 to 14,000, and more preferably 8,000 to 14,000. By making the number average molecular weight 7,000 or more, it is possible to obtain high mechanical strength and antifreeze resistance, and also to suppress the occurrence of mold deposits. By making the number average molecular weight 14,000 or less, it is possible to obtain high antifreeze resistance and appropriate fluidity.
[0087] Among them, PPS resins having the following characteristic (1) can reduce the amount of volatile components when the PPS resin composition is melted and can provide high antifreeze resistance. They are also preferred in the sense that they can suppress the occurrence of mold deposits. PPS resins having the following characteristic (2) can also suppress the occurrence of mold deposits and are also preferred from the viewpoints of obtaining high weld strength and antifreeze resistance.
[0088] (1) When the sample is dissolved in 20 times its weight of 1-chloronaphthalene at 250°C for 5 minutes and then pressure filtered through a PTFE membrane filter with a pore size of 1 μm under hot pressure, the residue amount is 2.0 to 5.0% by weight or less.
[0089] The residual amount of the PPS resin is preferably 4.8% by weight or less, more preferably 4.5% by weight or less. By setting the residual amount in the above-mentioned preferred range, it is preferable to obtain suitable fluidity. The lower limit of the residual amount is 2.0% by weight or more, preferably 2.2% by weight or more, more preferably 2.5% by weight or more. By setting the residual amount to 2.0% by weight or more, crosslinking by thermal oxidation treatment is promoted, volatile components during melting are reduced, and high antifreeze resistance can be obtained. A PPS resin having such properties can be obtained by appropriately applying a thermal oxidation treatment after the above-mentioned post-treatment process.
[0090] The amount of residue is measured by using a sample of PPS resin pressed into a film of about 80 μm thickness, a high-temperature filtration device, and a SUS test tube equipped with an air pressure cap and a collection funnel. Specifically, a membrane filter with a pore size of 1 μm is first set in a SUS test tube, and then PPS resin pressed into a film of about 80 μm thickness and 20 times the weight of 1-chloronaphthalene are weighed and sealed. This is set in a high-temperature filtration device at 250°C and heated and shaken for 5 minutes. Next, a syringe containing air is connected to the air pressure cap, and the piston of the syringe is pushed out to perform hot filtration by air pressure. The amount of residue is determined by the weight difference between the membrane filter before filtration and the membrane filter vacuum-dried at 150°C for 1 hour after filtration.
[0091] (2) When heated and melted in a vacuum at 320°C for two hours, the amount of volatile gas generated is 0.35% by weight or less.
[0092] The amount of gas generated from the PPS resin is preferably 0.30% by weight or less, more preferably 0.28% by weight or less. The PPS resin having such properties can be obtained by appropriately applying the above-mentioned cleaning and thermal oxidation treatment. By making the amount of gas generated 0.35% by weight or less, the volatile components are reduced, and the weld strength and antifreeze resistance are improved, which is preferable. The lower limit of the amount of gas generated after the thermal oxidation treatment is preferably small, but the preferred lower limit is 0.01% by weight. By making it 0.01% by weight or more, it is possible to prevent the thermal oxidation treatment time from becoming too long, which is economically disadvantageous. In addition, it is also preferable in terms of preventing this, since gelation is likely to occur due to the prolonged thermal oxidation treatment time, which is one of the factors that cause molding defects.
[0093] The gas generation amount means the amount of adhesive components that are liquefied or solidified by cooling the gas that volatilizes when PPS resin is heated and melted under vacuum, and is measured by heating a glass ampoule in which PPS resin is vacuum-sealed in a tubular furnace. The shape of the glass ampoule is 100 mm x 25 mm for the abdomen, 255 mm x 12 mm for the neck, and 1 mm thick. The specific measurement method is to insert only the body of the glass ampoule in which PPS resin is vacuum-sealed in a tubular furnace at 320°C and heat it for 2 hours, so that the volatile gas is cooled and adheres to the neck of the ampoule that is not heated by the tubular furnace. The neck is cut out and weighed, and the attached gas is dissolved in chloroform and removed. The neck is then dried and weighed again. The amount of gas generation is calculated from the difference in weight of the neck of the ampoule before and after gas removal.
[0094] For example, by employing the above-mentioned production method, it is possible to obtain a resin composition that not only has excellent antifreeze resistance but also suppresses the occurrence of mold deposits, using the obtained PPS resin, and it is preferable to use such a heat-treated PPS resin in the present invention.
[0095] The PPS resin blended in the PPS resin composition of the present invention must be (A) PPS resin having a number average molecular weight of 7,000 to 14,000 and a residue amount of 2.0 to 5.0% by weight when hot-pressurized filtered by the above-mentioned method, but (A) PPS resin may be only one type of PPS resin having the above-mentioned properties, or may be a mixture of multiple types of PPS resins having different properties. When multiple types of PPS resins are mixed, they may contain PPS resins that do not have the above-mentioned properties individually, as long as the PPS resin in the mixed state has the above-mentioned properties.
[0096] The PPS resin composition of the present invention contains (B) glass fibers.
[0097] The blending amount of (B) glass fiber in the PPS resin composition of the present invention is 30 to 110 parts by weight per 100 parts by weight of (A) PPS resin, which is necessary in order to obtain excellent mechanical strength, weld strength, and dimensional accuracy.
[0098] If the amount of (B) glass fiber is less than 30 parts by weight per 100 parts by weight of (A) PPS resin, the composition will not have adequate strength, and if the amount of (B) glass fiber is more than 110 parts by weight, the composition will have poor melt flowability, will not have adequate moldability, and will not have sufficient mechanical strength.
[0099] Specific examples of the (B) glass fiber include glass fiber, glass flat fiber, modified cross-section glass fiber, glass cut fiber, and flat glass fiber, and two or more of these can be used in combination. Among these, glass fiber is preferred. In addition, it is preferable to pretreat these glass fibers with a coupling agent such as an isocyanate compound, an organic silane compound, an organic titanate compound, an organic borane compound, and an epoxy compound in order to obtain better mechanical strength, and it is particularly preferable to treat them with a binder containing an epoxy group.
[0100] The PPS resin composition of the present invention comprises: Isocyanate functional group(hereinafter, also referred to as silane compound (C)).
[0101] The amount of the silane compound (C) in the PPS resin composition of the present invention is 0.1 to 3 parts by weight per 100 parts by weight of the PPS resin (A). By using such an amount, it is possible to simultaneously achieve excellent fluidity and antifreeze resistance.
[0102] If the amount of the silane compound (C) is less than 0.1 parts by weight per 100 parts by weight of the PPS resin (A), the composition will not have adequate strength or antifreeze resistance.If the amount of the silane compound (C) is more than 3 parts by weight, the melt flowability of the composition will decrease, the composition will not have adequate moldability, and mold deposits will increase.
[0103] Specific examples of the silane compound (C) include isocyanate group-containing alkoxysilane compounds such as γ-isocyanate propyl triethoxysilane, γ-isocyanate propyl trimethoxysilane, γ-isocyanate propyl methyl dimethoxysilane, γ-isocyanate propyl methyl diethoxysilane, γ-isocyanate propyl ethyl dimethoxysilane, γ-isocyanate propyl ethyl diethoxysilane, and γ-isocyanate propyl trichlorosilane. but Among them are Gamma Isocyanatepropyltriethoxysilane is particularly suitable for suppressing the occurrence of mold deposits in addition to providing excellent antifreeze resistance.
[0104] To the PPS resin composition of the present invention, an elastomer may be added for the purpose of improving thermal shock resistance, within a range that does not impair the effects of the present invention. Examples of such elastomers include (co)polymers obtained by polymerizing α-olefins such as ethylene, propylene, 1-butene, 1-pentene, 1-octene, 4-methyl-1-pentene, and isobutylene alone or two or more kinds of them, such as ethylene / propylene copolymers (" / " indicates copolymerization, the same applies below), ethylene / 1-butene copolymers, ethylene / 1-hexene copolymers, and ethylene / 1-octene copolymers. Also, it can be obtained by introducing a monomer component having an epoxy group (functional group-containing component) into a copolymer of an α-olefin and an α,β-unsaturated acid such as acrylic acid, methyl acrylate, ethyl acrylate, butyl acrylate, methacrylic acid, methyl methacrylate, ethyl methacrylate, or butyl methacrylate, or an alkyl ester thereof, for example, an ethylene / methyl acrylate copolymer, an ethylene / ethyl acrylate copolymer, an ethylene / butyl acrylate copolymer, an ethylene / methyl methacrylate copolymer, an ethylene / ethyl methacrylate copolymer, or an ethylene / butyl methacrylate copolymer, and examples of the functional group-containing component include monomers containing an epoxy group such as glycidyl acrylate, glycidyl methacrylate, glycidyl ethacrylate, glycidyl itaconate, and glycidyl citracone. There is no particular restriction on the method of introducing these functional group-containing components, and methods such as copolymerization during (co)polymerization of an olefin-based (co)polymer or graft introduction into an olefin-based (co)polymer using a radical initiator can be used. The amount of the functional group-containing component introduced is suitably within the range of 0.001 to 40 mol %, preferably 0.01 to 35 mol %, based on the total monomers constituting the modified olefin (co)polymer.Particularly useful specific examples of olefin copolymers having a glycidyl group obtained by introducing a monomer component having an epoxy group into an olefin polymer include ethylene / propylene-g-glycidyl methacrylate copolymer ("g" represents graft, same below), ethylene / 1-butene-g-glycidyl methacrylate copolymer, ethylene / glycidyl acrylate copolymer, ethylene / glycidyl methacrylate copolymer, ethylene / methyl acrylate / glycidyl methacrylate copolymer, ethylene / methyl methacrylate / glycidyl methacrylate copolymer, or epoxy group-containing olefin copolymers containing, in addition to an α-olefin such as ethylene or propylene and a glycidyl ester of an α,β-unsaturated acid, other monomers as essential components.
[0105] Preferred examples include ethylene / glycidyl methacrylate copolymer, ethylene / methyl acrylate / glycidyl methacrylate copolymer, ethylene / methyl methacrylate / glycidyl methacrylate copolymer, etc. Particularly preferred examples include ethylene / methyl acrylate / glycidyl methacrylate copolymer.
[0106] The amount of such elastomer to be added is preferably 1 to 20 parts by weight, and more preferably 2 to 15 parts by weight, for achieving excellent mechanical strength, resistance to cold and heat shocks, and moldability, relative to 100 parts by weight of the (A) PPS resin.
[0107] Furthermore, the PPS resin composition of the present invention may be blended with other resins as long as the effects of the present invention are not impaired. There are no particular limitations on the resins that can be blended, and specific examples include polyamide resins such as nylon 6, nylon 66, nylon 610, nylon 11, nylon 12, and aromatic nylons, polyester resins such as polyethylene terephthalate, polybutylene terephthalate, polycyclohexyldimethylene terephthalate, and polynaphthalene terephthalate, polyamideimide, polyacetal, polyimide, polyetherimide, polyethersulfone, modified polyphenylene ether resin, polysulfone resin, polyarylsulfone resin, polyketone resin, polyarylate resin, liquid crystal polymer, polyetherketone resin, polythioetherketone resin, polyetheretherketone resin, polyamideimide resin, and tetrafluoroethylene resin.
[0108] The PPS resin composition of the present invention may contain other components, for example, antioxidants and heat resistance stabilizers (hindered phenols, hydroquinones, phosphorus, phosphite, amines, sulfur, and their substituted derivatives, etc.), weathering agents (resorcinols, salicylates, benzotriazoles, benzophenones, hindered amines, etc.), release agents and lubricants (montanic acid and its metal salts, its esters, its half esters, stearyl alcohol, stearamide, stearates, bisurea, polyethylene wax, etc.), pigments (cadmium sulfide, phthalocyanine, coloring carbon black, etc.), dyes (nigrosine, etc.), crystal nucleating agents (inorganic crystal nucleating agents such as talc, silica, kaolin, clay, or other organic crystal nucleating agents), plasticizers (octyl p-oxybenzoate, N-butylbenzenesulfonamide, etc.), antistatic agents (alkyl sulfate-type aniline, etc.), etc.), as long as the effects of the present invention are not impaired. It is possible to add ordinary additives such as ionic antistatic agents, quaternary ammonium salt-type cationic antistatic agents, nonionic antistatic agents such as polyoxyethylene sorbitan monostearate, betaine-type amphoteric antistatic agents, etc.), flame retardants (e.g., red phosphorus, phosphate esters, melamine cyanurate, hydroxides such as magnesium hydroxide and aluminum hydroxide, ammonium polyphosphate, brominated polystyrene, brominated polyphenylene ether, brominated polycarbonate, brominated epoxy resins, or combinations of these brominated flame retardants with antimony trioxide, etc.), heat stabilizers, lubricants such as calcium stearate, aluminum stearate, and lithium stearate, strength improvers such as bisphenol epoxy resins such as bisphenol A type, novolac phenol type epoxy resins, and cresol novolac type epoxy resins, ultraviolet inhibitors, colorants, flame retardants, and foaming agents. Among them, polyethylene as a mold release agent is preferable from the viewpoint of antifreeze resistance, and amide compounds are particularly preferable from the viewpoint of suppressing the occurrence of mold deposits in addition to antifreeze resistance. The type of crystal nucleating agent is not particularly limited, but examples include inorganic crystal nucleating agents and organic crystal nucleating agents, and organic crystal nucleating agents are particularly preferred from the viewpoints of antifreeze resistance and weld strength.The organic crystal nucleating agent used in the present invention includes sorbitol compounds and their metal salts; phosphate metal salts; rosin compounds; amide compounds such as oleic acid amide, acrylic acid amide, stearic acid amide, decanedicarboxylic acid dibenzoyl hydrazide, hexanedicarboxylic acid dibenzoyl hydrazide, 1,4-cyclohexanedicarboxylic acid dicyclohexyl amide, trimesic acid amide, anilide compounds, 2,6-naphthalenedicarboxylic acid dicyclohexyl amide, N,N'-dibenzoyl-1,4-diaminocyclohexane, N,N'-dicyclohexanecarbonyl-1,5-diaminonaphthalene, and octanedicarboxylic acid dibenzoyl hydrazide; ethylenediamine-stearic acid-sebacic acid polycondensates; montanic acid waxes; and aliphatic carbonyl compounds. Examples of the organic compounds and polymer compounds include metal carboxylates, metal aromatic carboxylates, metal aromatic phosphonates and metal aromatic sulfonates, metal β-diketones, metal carboxylates, organic phosphorus compounds, polyethylene, polypropylene, polybutadiene, polystyrene, AS resins, ABS resins, poly(acrylic acid), poly(acrylic acid esters), poly(methacrylic acid), poly(methacrylic acid esters), polyamide 6, polyamide 46, polyamide 66, polyamide 6T, polyamide 9T, polyamide 10T, polyether ether ketone, and polyether ketone, among which polymer compounds having carbonyl groups are preferred, and polyether ether ketone is more preferred. The amount of the organic crystal nucleating agent is preferably 0.06 to 0.19 parts by weight per 100 parts by weight of the (A) PPS resin.
[0109] The PPS resin composition of the present invention may further contain other inorganic fillers than (B) glass fibers, as long as the effect of the present invention is not impaired. There is no particular restriction on the inorganic fillers that can be added, but specific examples of fibrous fillers as inorganic fillers include stainless steel fibers, aluminum fibers, brass fibers, rock wool, PAN-based and pitch-based carbon fibers, carbon nanotubes, carbon nanofibers, calcium carbonate whiskers, wollastonite whiskers, potassium titanate whiskers, barium titanate whiskers, aluminum borate whiskers, silicon nitride whiskers, aramid fibers, alumina fibers, silicon carbide fibers, asbestos fibers, gypsum fibers, ceramic fibers, zirconia fibers, silica fibers, titanium oxide fibers, and silicon carbide fibers, and two or more of these can be used in combination. In addition, it is preferable to pretreat these fibrous fillers with a coupling agent such as an isocyanate compound, an organic silane compound, an organic titanate compound, an organic borane compound, and an epoxy compound before use in order to obtain better mechanical strength.
[0110] Specific examples of non-fibrous fillers as inorganic fillers include talc, wollastonite, zeolite, sericite, mica, kaolin, clay, pyrophyllite, bentonite, asbestos, silicates such as alumina silicate and hydrotalcite, silicon oxide, magnesium oxide, aluminum oxide (alumina), silica (crushed and spherical), quartz, glass beads, glass flakes, crushed and irregularly shaped glass, glass microballoons, molybdenum disulfide, aluminum oxide (crushed), translucent alumina (fibrous, plate-like, scaly, granular, irregular, crushed), titanium oxide (crushed), zinc oxide (fibrous, plate-like, scaly, granular, irregular, crushed), Examples of the filler include oxides such as calcium carbonate, magnesium carbonate, and zinc carbonate, carbonates such as calcium sulfate and barium sulfate, hydroxides such as calcium hydroxide, magnesium hydroxide, and aluminum hydroxide, silicon carbide, carbon black and silica, graphite, aluminum nitride, translucent aluminum nitride (fibrous, plate-like, scaly, granular, irregularly shaped, crushed products), calcium polyphosphate, graphite, metal powder, metal flakes, metal ribbons, and metal oxides. Specific examples of the metal species of the metal powder, metal flakes, and metal ribbons include silver, nickel, copper, zinc, aluminum, stainless steel, iron, brass, chromium, and tin. Examples of the filler include carbon powder, graphite, carbon flakes, scaly carbon, fullerene, and graphene, which may be hollow, and two or more of these fillers may be used in combination. These inorganic fillers may also be pretreated with a coupling agent such as an isocyanate compound, an organic silane compound, an organic titanate compound, an organic borane compound, and an epoxy compound before use. Of these, calcium carbonate, carbon powder, and graphite are preferred.
[0111] There is no particular restriction on the method for preparing the PPS resin composition of the present invention, but a representative example is a method in which each raw material is fed to a commonly known melt mixer such as a single-screw or twin-screw extruder, a Banbury mixer, a kneader, and a mixing roll, and kneaded at a temperature of 280 to 380°C. There is also no particular restriction on the order in which the raw materials are mixed, and any of the following methods may be used: a method in which all raw materials are mixed and then melt-kneaded by the above method, a method in which some raw materials are mixed and then melt-kneaded by the above method, and the remaining raw materials are further mixed and melt-kneaded, or a method in which some raw materials are mixed and then the remaining raw materials are mixed using a side feeder while being melt-kneaded by a single-screw or twin-screw extruder. In addition, it is of course possible to add a small amount of additive components before molding after kneading other components by the above method and pelletizing them, and then subject them to molding.
[0112] The PPS resin composition of the present invention thus obtained can be subjected to various molding processes such as injection molding, extrusion molding, blow molding, and transfer molding, but is particularly suitable for injection molding. The PPS resin composition of the present invention is suitable for automobile cooling parts, particularly automobile cooling parts having a small and complex shape in which a plurality of parts are combined. The automobile cooling parts having a complex shape referred to here are, for example, a combination of a housing and at least two pipes, and the shape of the housing may be any shape such as a square shape, a triangular shape, an elliptical shape, or a composite shape of each of these. The housing may have a rib, a boss, or a flange, or may have a shape close to a flat surface. The shape of the pipe connected to the housing may be straight or curved, and the cross-sectional shape of the pipe may be any shape such as a circle, an ellipse, or a square shape. The pipe may have a rib, a boss, or a flange. The at least two or more pipes may have the same shape or a combination of different shapes. The pipes may be connected by, for example, bolt fastening, welding such as hot plate welding, or injection molding to form a part of the housing. The pipe may be connected to the wall or bottom surface. The lid of the housing may be made of resin or metal, and may be fastened by bolts or by welding such as hot plate welding.
[0113] Also, a housing, a valve, and at least three pipes are combined, and the shape of the housing may be any shape such as a square shape, a triangular shape, an elliptical shape, or a composite shape of each of them, and a rib, a boss, or a flange may be provided on the housing. The shape of the valve contained in the housing may be any shape such as a sphere shape, a cylindrical shape, or a composite shape of each of them, and the valve may have a hole. The number of valves may be one, or two or more. The shape of the pipe connected to the housing may be straight or curved, and the cross-sectional shape of the pipe may be any shape such as a circle shape, an ellipse shape, or a square shape. The pipe may be provided with a rib, a boss, or a flange. The at least three pipes may each have the same shape or a combination of different shapes. The pipes may be connected by, for example, bolt fastening, welding such as hot plate welding, or injection molding to form a part of the housing. The method of enclosing the valve may involve dividing the housing into a case and a lid, enclosing the valve inside the case, and bolting the lid to form the housing, or the lid may be welded by hot plate welding or the like to form the housing.
[0114] The liquid flowing inside the housing may be water or an antifreeze liquid containing alcohols, glycols, glycerin, etc., and the type and concentration of the liquid are not particularly limited. In addition, the liquid may be high temperature or low temperature, and may flow repeatedly. The valve contained in the housing may be opened and closed using the driving force of the engine or the driving force of the motor.
[0115] The melt crystallization peak temperature of the PPS resin composition of the present invention, as determined by a differential scanning calorimeter, is preferably 230°C, more preferably 235°C or higher. A melt crystallization peak temperature of 230°C or higher is preferable because it shortens the cooling time during injection molding, improving productivity, and also improves antifreeze resistance. In order to obtain a PPS resin composition having such characteristics, for example, it is considered to blend an organic crystal nucleating agent. The melt crystallization peak temperature in the present invention is a value measured by taking about 10 mg of a sample from a pellet of the PPS resin composition, heating it at a heating rate of 20°C / min using a differential scanning calorimeter DSC-7 manufactured by PerkinElmer, and holding it at 340°C for 5 minutes, and then cooling it at a rate of 20°C / min.
[0116] The PPS resin composition of the present invention preferably has a tensile strength of 190 MPa or more in an ISO test piece obtained by injection molding the PPS resin composition. When the tensile strength of the ISO test piece is in the above-mentioned preferred range, the molded product can have sufficient strength. In this case, the tensile strength is evaluated based on the tensile strength measured at a pulling speed of 5 mm / min and an ambient temperature of 23° C. in accordance with ISO 527-1, -2. The ISO test piece is immersed in an antifreeze solution at 150° C. for 500 hours, and then the tensile strength is measured at a pulling speed of 5 mm / min and an ambient temperature of 23° C. in accordance with ISO 527-1, -2. The strength retention of the tensile strength after the antifreeze solution treatment is preferably 80% or more. When the strength retention of the tensile strength after the antifreeze solution treatment is in the above-mentioned preferred range, the mechanical strength is unlikely to decrease due to the antifreeze solution treatment, and the molded product does not become a crack starting point. It is particularly preferable that the tensile strength is 190 MPa or more and the retention rate of the tensile strength after antifreeze treatment is 80% or more, since it combines superior mechanical strength with resistance to hot water and antifreeze. In order to obtain a PPS resin composition with such characteristics, it is possible to consider blending, for example, a PPS resin having a number average molecular weight of 7,000 to 14,000 that has been thermally oxidized with glass fibers.
[0117] There are no particular restrictions on the type of antifreeze; it may be Volkswagen genuine LLC (G13), Toyota genuine S-LLC, General Motors genuine LLC (Dex-cool), or Hyundai genuine LLC (A-110).
[0118] As described above, the PPS resin composition of the present invention is excellent not only in mechanical strength but also in antifreeze resistance and can suppress the occurrence of mold deposits. That is, the PPS resin composition of the present invention has high mechanical strength and high antifreeze resistance, and also suppresses the occurrence of mold deposits, and is therefore useful for automotive cooling parts, and is particularly useful for automotive cooling parts that are small and have complex shapes and are made up of multiple parts.
[0119] Other applications for the PPS resin composition of the present invention include electric and electronic components such as sensors, LED lamps, consumer connectors, sockets, resistors, relay cases, switches, coil bobbins, capacitors, variable capacitor cases, oscillators, various terminal boards, transformers, plugs, printed circuit boards, tuners, speakers, microphones, headphones, small motors, magnetic head bases, semiconductors, liquid crystal, FDD carriages, FDD chassis, motor brush holders, parabolic antennas, and computer-related components; VTR components, television components, irons, hair dryers, rice cooker components, microwave oven components, audio components, audio equipment components such as audio, laser discs (registered trademark), and compact discs, lighting components, refrigerator components, air conditioner components, typewriter components, and word processor components, as well as home and office electrical appliance components.Others include office computer parts, telephone parts, facsimile parts, copier parts, cleaning tools, motor parts, lighters, typewriters and other machinery parts; optical equipment such as microscopes, binoculars, cameras, clocks, precision machinery parts; water faucet tops, mixer faucets, pump parts, pipe joints, water flow control valves, relief valves, water temperature sensors, water flow sensors, water meter housings and other plumbing parts; valve alternator terminals, alternator connectors, IC regulators, light dimmer potentiometer bases, exhaust gas valves and other valves; various fuel, exhaust and intake system pipes; air intake nozzle snorkels, intake manifolds, fuel pumps, engine coolant joints, carburetor main bodies, carburetor spacers, exhaust gas sensors, coolant sensors, oil temperature sensors Examples of applications include automobile and vehicle related parts such as throttle position sensors, crankshaft position sensors, air flow meters, brake pad wear sensors, air conditioner thermostat bases, heating hot air flow control valves, radiator motor brush holders, water pump impellers, turbine vanes, wiper motor related parts, distributors, starter switches, starter relays, transmission wire harnesses, windshield washer nozzles, air conditioner panel switch boards, coils for fuel-related electromagnetic valves, fuse connectors, horn terminals, electrical component insulating plates, step motor rotors, lamp sockets, lamp reflectors, lamp housings, brake pistons, solenoid bobbins, engine oil filters, ignition device cases, vehicle speed sensors, and cable liners. EXAMPLES
[0120] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the descriptions of these examples.
[0121] [Method of measuring PPS resin] (1) Residual amount A pre-weighed PTFE membrane filter with a pore size of 1 μm was placed in a Senshu Scientific SUS test tube equipped with an air pressure cap and a collection funnel, and 100 mg of PPS resin pressed into a film of about 80 μm thickness and 2 g of 1-chloronaphthalene were weighed and then sealed. This was inserted into a Senshu Scientific high-temperature filtration device SSC-9300 and heated and shaken at 250 °C for 5 minutes to dissolve the PPS resin in the 1-chloronaphthalene. After connecting a 20 mL syringe containing air to the air pressure cap, the piston was pushed out to filter the solution through the membrane filter. The membrane filter was removed, vacuum dried at 150 °C for 1 hour, and then weighed. The difference in the weight of the membrane filter before and after filtration compared to the weight of the membrane filter before filtration was taken as the residue (wt%).
[0122] (2) Amount of gas generated 3g of PPS resin was weighed and placed in a glass ampoule with a body of 100mm x 25mm, a neck of 255mm x 12mm, and a wall thickness of 1mm, and then vacuum sealed. Only the body of this glass ampoule was inserted into a ceramic electric tubular furnace ARF-30K manufactured by Asahi Rika Seisakusho and heated at 320℃ for 2 hours. After removing the ampoule, the neck of the ampoule, which had not been heated by the tubular furnace and had volatile gas attached to it, was cut out with a file and weighed. The attached gas was then dissolved and removed with 5g of chloroform, dried in a glass dryer at 60℃ for 1 hour, and then weighed again. The difference in weight of the ampoule neck before and after gas removal was taken as the amount of gas generated (wt%).
[0123] (3) Melt flow rate (MFR) The measurement was performed at a measurement temperature of 315.5°C under a load of 5,000 g in accordance with ASTM-D1278-70.
[0124] (4) Number average molecular weight Gel permeation chromatography measurement: Using a WATERS (GPC-244) device, a Shodex K-806M (Showa Denko) column, 1-chloronaphthalene solvent, and a hydrogen flame ionization detector, the number average molecular weight was measured according to the method described in the Polymer Journal, Vol. 44 (1987), February issue, pp. 139-141, using six types of monodisperse polystyrene for calibration.
[0125] [Reference Example 1] Polymerization of PPS (PPS-1) In an autoclave equipped with a stirrer and a valve at the bottom, 8,267.4g (70.0 mol) of 47.5% sodium hydrosulfide, 2,925.0g (70.2 mol) of 96% sodium hydroxide, 13,860.0g (140.0 mol) of N-methyl-2-pyrrolidone (NMP), 1894.2g (23.1 mol) of sodium acetate, and 10,500.0g of ion-exchanged water were charged, and the mixture was gradually heated to 240°C over about 3 hours while passing nitrogen through it at normal pressure. After distilling out 14,772.1g of water and 280.0g of NMP, the reaction vessel was cooled to 160°C. The amount of water remaining in the system per mole of charged alkali metal sulfide was 1.08 mol, including the water consumed in the hydrolysis of NMP. The amount of hydrogen sulfide scattered was 0.023 mol per mole of charged alkali metal sulfide.
[0126] Next, 10,646.7 g (72.4 mol) of p-dichlorobenzene (p-DCB) and 6,444.9 g (65.1 mol) of NMP were added, the reaction vessel was sealed under nitrogen gas, and the temperature was raised from 200° C. to 270° C. at a rate of 0.6° C. / min while stirring at 240 rpm, and the temperature was maintained at 270° C. for 70 minutes. The extraction valve at the bottom of the autoclave was opened, and the contents were flushed into a vessel equipped with a stirrer over 15 minutes while pressurizing with nitrogen, and most of the NMP was removed by stirring at 250° C. for a while.
[0127] The obtained solid matter and 53 L of ion-exchanged water were placed in an autoclave equipped with a stirrer, washed at 70°C for 30 minutes, and then suction filtered through a glass filter with a pore size of 10 to 16 μm. Next, 60 L of ion-exchanged water heated to 70°C was poured into a glass filter with a pore size of 10 to 16 μm, and suction filtered to obtain 18,000 g of PPS resin cake (including 7,550 g of PPS resin).
[0128] 18,000 g of the PPS resin cake, 40 L of ion-exchanged water, and 43 g of acetic acid were charged into an autoclave equipped with a stirrer, and the inside of the autoclave was replaced with nitrogen, and then the temperature was raised to 192°C and held for 30 minutes to perform acid treatment. The pH during the acid treatment was 7. After cooling the autoclave, the contents were filtered through a glass filter with a pore size of 10 to 16 μm. Next, 60 L of ion-exchanged water heated to 70°C was poured into the glass filter, and suction filtration was performed to obtain a cake. The obtained cake was dried at 120°C for 4 hours under a nitrogen stream to obtain a powder of PPS resin subjected to acid treatment. Next, this PPS resin powder was placed in a heating device equipped with a stirrer with a volume of 100 L and subjected to thermal oxidation treatment at 220°C and an oxygen concentration of 2% for 2 hours to obtain a crosslinked PPS-1. The number average molecular weight of the obtained polymer was 8,500, the amount of gas generated was 0.16% by weight, the amount of residue was 2.1% by weight, and the MFR was 420 g / 10 min.
[0129] [Reference Example 2] Polymerization of PPS (PPS-2) In a 70L autoclave equipped with a stirrer and a bottom plug valve, 8.27 kg (70.00 mol) of 47.5% sodium hydrosulfide, 2.91 kg (69.80 mol) of 96% sodium hydroxide, 11.45 kg (115.50 mol) of N-methyl-2-pyrrolidone (NMP), and 10.5 kg of ion-exchanged water were charged, and the mixture was gradually heated to 245°C over about 3 hours while passing nitrogen through it at normal pressure. After distilling out 14.78 kg of water and 0.28 kg of NMP, the reaction vessel was cooled to 200°C. The amount of water remaining in the system per mole of charged alkali metal sulfide was 1.06 mol, including the water consumed in the hydrolysis of NMP. The amount of hydrogen sulfide scattered was 0.02 mol per mole of charged alkali metal sulfide.
[0130] The mixture was then cooled to 200°C, 10.48 kg (71.27 mol) of p-dichlorobenzene and 9.37 kg (94.50 mol) of NMP were added, the reaction vessel was sealed under nitrogen gas, and the temperature was increased from 200°C to 270°C at a rate of 0.6°C / min while stirring at 240 rpm. After reacting for 100 minutes at 270°C, the bottom plug valve of the autoclave was opened, and the contents were flushed into a vessel equipped with a stirrer over 15 minutes while pressurizing with nitrogen, and most of the NMP was removed by stirring for a while at 250°C.
[0131] The obtained solid matter and 76 L of ion-exchanged water were placed in an autoclave equipped with a stirrer, washed at 70°C for 30 minutes, and then suction filtered through a glass filter. Next, 76 L of ion-exchanged water heated to 70°C was poured into the glass filter, and suction filtered to obtain a cake.
[0132] The obtained cake and 90 L of ion-exchanged water were charged into an autoclave equipped with a stirrer, and acetic acid was added to adjust the pH to 7. After replacing the inside of the autoclave with nitrogen, the temperature was raised to 192°C and maintained at that temperature for 30 minutes. The autoclave was then cooled and the contents were removed.
[0133] The contents were filtered with a glass filter, and then 76 L of 70°C ion-exchanged water was poured into the filter and filtered with aspiration to obtain a cake. The cake was dried at 120°C under a nitrogen stream to obtain a dried PPS. This was heat-treated at 200°C under an oxygen stream until the MFR value reached 150g / 10min to obtain a crosslinked PPS-2. The number-average molecular weight of the obtained polymer was 11,500, the amount of gas generated was 0.39% by weight, the amount of residue was 5.9% by weight, and the MFR was 140g / 10min.
[0134] [Reference Example 3] Polymerization of PPS (PPS-3) Linear PPS-3 was obtained in the same manner as in Reference Example 2, except that the heat treatment was performed at 200° C. under an oxygen stream. The number average molecular weight of the obtained polymer was 8,000, the amount of gas generated was 0.44% by weight, the amount of residue was 1.5% by weight, and the MFR was 720 g / 10 min.
[0135] [Reference Example 4] Polymerization of PPS (PPS-4) An autoclave was charged with 4.67 kg (25 moles of sodium hydrosulfide) of 30% aqueous sodium hydrosulfide solution, 2.00 kg (25 moles of sodium hydroxide) of 50% sodium hydroxide, and 8 kg of N-methyl-2-pyrrolidone (NMP), and the temperature was gradually raised to 205°C while stirring, and 4.11 kg of distillate containing 3.8 kg of water was removed. 3.75 kg (25.5 moles) of 1,4-dichlorobenzene and 2 kg of NMP were added to the remaining mixture, and the mixture was heated at 230°C for 1 hour and then at 260°C for 30 minutes. The reaction product was washed five times with warm water and dried under reduced pressure at 80°C for 24 hours to obtain a powdered linear PPS-4 with a number average molecular weight of 3,700. The number average molecular weight of the obtained polymer was 3,700, the amount of gas generated was 0.54% by weight, the amount of residue was 1.3% by weight, and the MFR was 9,570g / 10min.
[0136] [Reference Example 5] Polymerization of PPS (PPS-5) In a 70L autoclave equipped with a stirrer, 8,267.37g (70.0 mol) of 47.5% sodium hydrosulfide, 2,962.50g (71.10 mol) of 96% sodium hydroxide, 11,434.50g (115.50 mol) of N-methyl-2-pyrrolidone (NMP), 516.60g (6.30 mol) of sodium acetate, and 10,500g of ion-exchanged water were charged, and the mixture was gradually heated to 230°C over about 3 hours while passing nitrogen through it at normal pressure. After distilling out 14,780.1g of water and 280g of NMP, the reaction vessel was cooled to 160°C. The amount of water remaining in the system per mole of charged alkali metal sulfide was 1.06 mol, including the water consumed in the hydrolysis of NMP. The amount of hydrogen sulfide scattered was 0.017 mol per mole of charged alkali metal sulfide.
[0137] Next, 10,363.50g (70.5 mol) of p-dichlorobenzene and 9,078.30g (91.7 mol) of NMP were added, the reaction vessel was sealed under nitrogen gas, and the temperature was raised to 270°C at a rate of 0.6°C / min while stirring at 240 rpm, and the temperature was maintained at 270°C for 140 minutes. Then, 2,520g (140 mol) of ion-exchanged water was pressed into the autoclave while cooling to 250°C at a rate of 1.3°C / min. Then, the mixture was cooled to 200°C at a rate of 1.0°C / min, and then quenched to near room temperature.
[0138] The contents were taken out and diluted with 26,300g of NMP, after which the solvent and solids were filtered through a sieve (80 mesh), and the resulting particles were washed with 31900g of NMP and filtered. This was washed and filtered several times with 56,000g of ion-exchanged water, and then washed and filtered with 70,000g of 0.05% by weight of acetic acid aqueous solution. After washing and filtering with 70,000g of ion-exchanged water, the resulting hydrous PPS particles were dried with hot air at 80°C and dried under reduced pressure at 120°C to obtain linear PPS-5. The number average molecular weight of the resulting polymer was 7,700, the amount of gas generated was 0.11% by weight, the amount of residue was 0.02% by weight, and the MFR was 580g / 10min.
[0139] [Reference Example 6] Polymerization of PPS (PPS-6) A linear PPS-6 was obtained in the same manner as in Reference Example 5, except that 1,722.00 g (21.00 mol) of sodium acetate was added. The number average molecular weight of the obtained polymer was 8,900, the amount of gas generated was 0.09 wt%, the amount of residue was 0.02 wt%, and the MFR was 210 g / 10 min.
[0140] [Formulations used in the Examples and Comparative Examples] The compositions used in the present examples and comparative examples are as follows:
[0141] (A)PPS resin PPS-1: PPS resin polymerized by the method described in Reference Example 1 PPS-2: PPS resin polymerized by the method described in Reference Example 2 PPS-3: PPS resin polymerized by the method described in Reference Example 3 PPS-4: PPS resin polymerized by the method described in Reference Example 4 PPS-5: PPS resin polymerized by the method described in Reference Example 5 PPS-6: PPS resin polymerized by the method described in Reference Example 6 (B) Glass fiber B: Chopped strand (T-760H, Nippon Electric Glass Co., Ltd., 3 mm long, average fiber diameter 10.5 μm) (C) Silane Compound C-1: 3-aminopropyltriethoxysilane (KBE-903, manufactured by Shin-Etsu Chemical Co., Ltd.) C-2: 3-isocyanatepropyltriethoxysilane (KBE-9007, manufactured by Shin-Etsu Chemical Co., Ltd.) (D) Additives D-1: Polyethylene (Hi-Zex 7000FP, manufactured by Mitsui Chemicals, Inc.) D-2: Amide compound (Kyoeisha Chemical Co., Ltd. Light Amide WH500) D-3: Organic crystal nucleating agent (polyether ether ketone PEEK450-PF, manufactured by Victrex MC).
[0142] [Measurement and evaluation method] The measurement and evaluation methods in the present examples and comparative examples are as follows.
[0143] (1) Tensile strength Measurements were performed in accordance with ISO 527-1, 2 (2012). Specifically, measurements were performed as follows. The PPS resin composition pellets of the present invention were dried at 130°C for 3 hours using a hot air dryer, and then fed to an injection molding machine (SE-50D) manufactured by Sumitomo Heavy Industries, Ltd., with a cylinder temperature of 310°C and a mold temperature of 145°C. Using a mold with a type A1 test piece shape (4 mm thick) specified in ISO20753 (2008), injection molding was performed under conditions in which the average speed of the molten resin passing through the cross-sectional area of the central parallel part was 400±50 mm / s, to obtain a test piece. The test piece was conditioned for 16 hours under conditions of 23°C and 50% relative humidity, and then tensile strength was measured in accordance with ISO 527-1, -2 (2012) under conditions of 23°C, 50% relative humidity, gripper distance: 115 mm, and test speed: 5 mm / min. A strength of 185 MPa or more can be said to be at a level sufficient for practical use as a product, but the higher this value, the better the mechanical strength and the more preferable it is.
[0144] (2) Tensile strength retention The antifreeze was prepared by diluting Volkswagen genuine LLC (G13) with distilled water to a 50% by weight aqueous solution. After immersing a test piece of type A1 test piece shape (4 mm thick) specified in ISO 20753 in antifreeze at a temperature of 150 ° C for 500 hours, the liquid adhering to the test piece was wiped off, and the test piece was conditioned for 16 hours at 23 ° C and 50% relative humidity. The tensile strength was measured in accordance with ISO 527-1, -2 under the conditions of 23 ° C and 50% relative humidity, gripper distance: 115 mm, and test speed: 5 mm / min. The value calculated from (tensile strength after antifreeze immersion treatment / tensile strength described in (1)) was expressed as a percentage, and this value was taken as the tensile strength retention rate. If it is 75% or more, it can be said that the product level is satisfactory for practical use, but the higher this value, the better the antifreeze resistance and the more preferable it is.
[0145] (3) Mold staining In the mold for gas evaluation of the molded product shown in FIG. 1 (molded product size: length 55 mm, width 20 mm, thickness 2 mm, gate size: width 2 mm, thickness 1 mm (side gate), maximum gas vent length 20 mm, width 10 mm, depth 5 μm), the cylinder temperature was 330°C, the mold temperature was 130°C, the injection speed was 100 mm / s, and the injection pressure was set within 50 to 80 MPa so that the filling time for each resin composition was 0.4 seconds. The mold contamination state of the mold gas vent was visually observed every 10 shots (molding machine used: Sumitomo Heavy Industries "SE-30D"). If the number of shots until adhesion is 100 or more, it can be said that it is at a level that can be used practically, but the greater the number of shots, the better the mold deposit property, which is preferable.
[0146] (4) Weld strength An ASTM No. 4 dumbbell specimen (1.6 mmt) with gates on both ends and a weld line near the center of the specimen was molded using an injection molding machine at a cylinder temperature of 320°C and a mold temperature of 135°C. Ten samples were obtained for measurement, and tensile strength was measured at a test speed of 10 mm / min and a gripper distance of 64 mm. A value of 65 MPa or higher is considered to be at a product level with no practical problems, but the higher this value, the better the mechanical strength and the more preferable it is.
[0147] (5) Liquidity Using a 1mm thick spiral flow mold, molding was performed under the following conditions: cylinder temperature 320℃, mold temperature 140℃, injection speed 230mm / sec, injection pressure 98MPa, injection time 5sec, cooling time 15sec, and flow length was measured (injection molding machine used: Sumitomo Heavy Industries "SE-30D"). The higher this value, the better the flowability.
[0148] (6) Melt crystallization peak temperature Approximately 10 mg of a sample was taken from the pellets of the PPS resin composition, and the sample was heated at a rate of 20°C / min using a PerkinElmer DSC-7 differential scanning calorimeter. The sample was then held at 340°C for 5 minutes and cooled at a rate of 20°C / min to measure the crystallization peak temperature, which was taken as the melt crystallization peak temperature.
[0149] [Production of PPS resin composition] (Examples 1 to 4. Reference Example 1 , Comparative Examples 1 to 10) Using a twin-screw extruder (TEM-26 manufactured by Toshiba Machine Co., Ltd.) with a 26 mm diameter middle addition port, with the cylinder temperature set at 320°C and the screw rotation speed set at 400 rpm, 100 parts by weight of the PPS resin (A) obtained in Reference Examples 1 to 6 was added from the raw material supply port in the weight ratio shown in Table 1 to be in a molten state, and (B) the inorganic filler was supplied from the middle addition port in the weight ratio shown in Table 1, and melt-kneaded at a discharge rate of 30 kg / hour to obtain pellets. The pellets were used to evaluate the above-mentioned properties. The results are shown in Tables 1 and 2.
[0150] [Table 1]
[0151] [Table 2] [Industrial Applicability]
[0152] The PPS resin composition thus obtained has high mechanical strength and antifreeze resistance, and also has the unknown property of suppressing the occurrence of mold deposits, and is therefore useful for automotive cooling parts, particularly for small, complex-shaped automotive cooling parts that combine multiple parts. [Explanation of symbols]
[0153] 1. Housing 2. Valves 3. Axis 4. Pipes 5. Hole 6. Packing 7. Cavity 8. Gate section
Claims
1. A polyphenylene sulfide resin composition for automobile cooling parts, comprising 100 parts by weight of (A) polyphenylene sulfide resin, 30 to 110 parts by weight of (B) glass fiber, and 0.1 to 3 parts by weight of (C) a silane compound having an isocyanate group as a functional group, wherein the number average molecular weight of the polyphenylene sulfide resin (A) is 7,000 to 14,000, and the polyphenylene sulfide resin composition has a residue amount of 2.0 to 5.0% by weight when the polyphenylene sulfide resin (A) is dissolved in 1-chloronaphthalene in an amount 20 times the weight of the polyphenylene sulfide resin at 250° C. for 5 minutes and pressure filtered under hot conditions using a PTFE membrane filter having a pore size of 1 μm.
2. 2. The polyphenylene sulfide resin composition according to claim 1, wherein the polyphenylene sulfide resin composition has a melt crystallization peak temperature of 230° C. or higher.
3. The polyphenylene sulfide resin composition according to claim 1 or 2, which satisfies both of the following conditions (i) and (ii): (i) The tensile strength measured using a type A1 test piece (hereinafter referred to as an ISO test piece) specified in ISO 20753 obtained by injection molding a polyphenylene sulfide resin composition at a tensile speed of 5 mm / min and an atmospheric temperature of 23° C. in accordance with ISO 527-1 and -2 methods is 190 MPa or more; (ii) After the ISO test piece is immersed in an antifreeze solution at 150° C. for 500 hours, the retention of tensile strength measured in accordance with ISO 527-1 and -2 at a tensile speed of 5 mm / min and an atmospheric temperature of 23° C. is 80% or more.
4. An automobile cooling part comprising the polyphenylene sulfide resin composition according to any one of claims 1 to 3.
5. 4. An automobile cooling part comprising a housing formed by injection molding the polyphenylene sulfide resin composition according to claim 1, and at least two pipes.
6. 4. An automobile cooling part comprising a housing formed by injection molding the polyphenylene sulfide resin composition according to claim 1, a valve, and at least three pipes.
Citation Information
Patent Citations
Poly@(3754 / 24)phenylene sulfide) resin composition
JP1994041425A
Polyarylene sulfide resin composition
JP2006219666A
Polyphenylene sulfide resin composition and molding
JP2010195874A
Polyphenylene sulfide resin composition, and method for manufacturing the same
JP2011153242A
Poly(phenylene sulfide) resin composition, production method therefor, and molded article
WO2018180591A1